2008
DOI: 10.1021/nl072941g
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hydrogen Storage Capacity of MOF by Functionalization of the Organic Linker with Lithium Atoms

Abstract: A combination of quantum and classical calculations have been performed in order to investigate hydrogen storage in metal-organic frameworks (MOFs) modified by lithium alkoxide groups. Ab initio calculations showed that the interaction energies between the hydrogen molecules and this functional group are up to three times larger compared with unmodified MOF. This trend was verified by grand canonical Monte Carlo (GCMC) simulations in various thermodynamic conditions. The gravimetric capacity of the Li-modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
205
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(212 citation statements)
references
References 43 publications
2
205
0
5
Order By: Relevance
“…Carbon based materials are candidates for such a purpose. Although several mechanisms of hydrogen storage through both physisorption and chemisorption have been proposed, [3][4][5][6][7] most of these efforts are far to reach the target of 6 wt% and immobilization hydrogen with binding strength of -0.2 ~ -0.4 eV/H 2 at ambient temperature and modest pressure for commercial applications specified by U.S. Department of Energy (DOE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon based materials are candidates for such a purpose. Although several mechanisms of hydrogen storage through both physisorption and chemisorption have been proposed, [3][4][5][6][7] most of these efforts are far to reach the target of 6 wt% and immobilization hydrogen with binding strength of -0.2 ~ -0.4 eV/H 2 at ambient temperature and modest pressure for commercial applications specified by U.S. Department of Energy (DOE).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Thus, the storage of hydrogen molecules by carbon nanostructures is still an important issue and deserves more attention. For example, the potential of graphene as hydrogen storage materials through doping is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…After publishing the paper on Li-doped MOFs, some similar theoretical works were reported. [164][165][166][167][168] Blomqvist et al 164 showed using DFT calculations that two Li atoms are strongly adsorbed on six-carbon rings of the organic linker in Zn 4 -based MOF-5, one on each site, carrying a charge of +0.9 e per Li, and each Li can bind three H 2 molecules around itself with a binding energy of 12 kJ mol À1 .…”
mentioning
confidence: 99%
“…165 However, another theoretical work 166 on Zn 2 -based MOFs reported the result that the Li associates strongly with the metal oxide part and less so with the aromatic rings. Klontzas et al 167 calculated the hydrogen storage amount in MOFs modified by lithium alkoxide groups, and the Li-modified MOFs have a high H 2 uptake of 10 wt% at 77 K and 100 bar and 4.5 wt% at room temperature. Choi et al 168 considered Li-doped COFs and showed using DFT calculations that Li doping plays a beneficial role to enhance H 2 uptake of COFs.…”
mentioning
confidence: 99%
“…Various ab initio calculations, grand canonical Monte Carlo and molecular dynamics simulations have recently shown that doping with alkali metals can enhance the fundamental interaction of H2 with the host structures in a desired range of magnitude [5,[34][35][36][37][38][39][40][41][42]. The mechanism can be generally attributed to electrostatic charge-quadrupole and charge induced dipole interactions, which is further related to the localization and polarizability between hydrogen and charged metal sites [43][44][45].…”
Section: Introductionmentioning
confidence: 99%